Heart Rate Variability Reveals Altered Autonomic Regulation in Response to Myocardial Infarction in Experimental Animals - Pizzo, Emanuele; Berrettoni, Silvia; Kaul, Ridhima; Cervantes, Daniel O.; Di Stefano, Valeria; Jain, Sudhir; Jacobson, Jason T.; Rota, Marcello (Frontiers in Cardiovascular Medicine, 2022)
The analysis of beating rate provides information on the modulatory action of the autonomic nervous system on the heart, which mediates adjustments of cardiac function to meet hemodynamic requirements. In patients with myocardial infarction, alterations of heart rate variability (HRV) have been correlated to the occurrence of arrhythmic events and all-cause mortality. In the current study, we tested whether experimental rodent models of myocardial infarction recapitulate dynamics of heart rate variability observed in humans, and constitute valid platforms for understanding mechanisms linking autonomic function to the development and manifestation of cardiovascular conditions. For this purpose, HRV was evaluated in two engineered mouse lines using electrocardiograms collected in the conscious, restrained state. Measurements were obtained in the naïve mice and animals at 3-~28 days following myocardial infarction, induced by permanent coronary artery ligation. Two mouse lines with inbred and hybrid genetic background and, respectively, homozygous (Homo) and heterozygous (Het) for the MerCreMer transgene, were employed. In the naïve state, Het female and male mice presented prolonged RR interval duration (~9%) and a ~4-fold increased short- and long-term RR interval variability, with respect to sex-matched Homo mice. These differences were abrogated by pharmacological interventions inhibiting the sympathetic and parasympathetic axes. At 3-~14 days after myocardial infarction, RR interval duration increased in Homo mice, but was not affected in Het animals. In contrast, Homo mice had minor modifications in HRV parameters, whereas substantial (>50%) reduction of short- and long-term RR interval variation occurred in Het mice. Interestingly, ex vivo studies in isolated organs documented that intrinsic RR interval duration increased in infarcted versus non-infarcted Homo and Het hearts, whereas RR interval variation was not affected. In conclusion, our study document that, as observed in humans, myocardial infarction in rodents is associated with alterations in heart rhythm dynamics consistent with sympathoexcitation and parasympathetic withdrawal. Moreover, we report that mouse strain is an important variable when evaluating autonomic function via the analysis of HRV.